Electrocardiographic characteristics and ablation of ventricular arrhythmias originating from the basal inferoseptal area. Issue 12 (2nd September 2021) - Larsen, Timothy R; Shepard, Richard K; Koneru, Jayanthi N; Cabrera, José-Angel; Ellenbogen, Kenneth A; Padala, Santosh K
Abstract: Aims : Ventricular arrhythmias (VAs) from the basal inferoseptal (BIS) area are rare and can pose unique challenges during catheter ablation (CA) due to the anatomic complexity. The study sought to describe the electrocardiographic and clinical characteristics of VAs originating from the BIS area. Methods and results : Patients with VAs and successful ablation at the BIS area from 2016 to 2020 were included. The 12-lead electrocardiogram (ECG), intracardiac findings, and outcomes were analysed. Of 482 patients with VAs referred for CA, 17 (3.5%) had successful ablation at BIS area. There were 12 males, mean age was 66.7 ± 9 years, 82% had ejection fraction <50%. Mean baseline premature ventricular complex burden was 28.6 ± 9%. All patients had a leftward superior axis. Left bundle branch block (LBBB) with early transition in V2 was noted in eight patients and right bundle branch block (RBBB) in nine patients. Detailed mapping of the right ventricle (RV) was performed in 15 patients (88%), coronary sinus (CS)/middle cardiac vein (MCV) in 13 (76%), right atrium (RA) adjacent to the inferoseptal process (ISP) of left ventricle (LV) in 5 (29%), ISP-LV in 13 (76%), and epicardium in 2 (12%). Successful ablation site was in LV in 10 (59%), RV in 2 (12%), CS/MCV in 1 (6%), RA in 1 (6%), and epicardium in 2 (12%). Fifteen patients (88%) required mapping in at least two chambers (range 2–5) and seven patients (41%) required ablation in at least two chambers (range 2–3). Conclusions : Ventricular arrhythmias originating in the BIS are uncommon. The most common ECG patterns were leftward superior axis, LBBB with transition in V2 or RBBB. The VA foci can be endocardial or epicardial and meticulous mapping/ablation from multiple chambers is often required to eliminate these foci successfully.